Sistem Informasi Penyewaan Indekos Terdekat dengan Kawasan Industri Berbasis Website di Bogor - Fiqri Hendrawan; Ziveria , Mira (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
Boarding rental systems in the Bogor industrial area still use traditional methods to order boarding houses. This study aims to build a web-based boarding house rental information system that includes boarding house marketing and boarding orders with the Watefall system development method which includes system analysis using cross-functional diagrams and causal diagrams, system design using the Unified Modeling Language (UML)), development system and programming using the Hypertext Preprocessor (PHP) programming language and the My Structure Query Language (MySQL) database and system testing using a black box with alpha testing. The results of this study are systems that can be used to order boarding houses online in Bogor.